2017
DOI: 10.24171/j.phrp.2017.8.6.06
|View full text |Cite
|
Sign up to set email alerts
|

Development of a New Approach to Determine the Potency of Bacille Calmette–Guérin Vaccines Using Flow Cytometry

Abstract: ObjectivesTo circumvent the limitations of the current golden standard method, colony-forming unit (CFU) assay, for viability of Bacille Calmette–Guérin (BCG) vaccines, we developed a new method to rapidly and accurately determine the potency of BCG vaccines.MethodsBased on flow cytometry (FACS) and fluorescein diacetate (FDA) as the most appropriate fluorescent staining reagent, 17 lots of BCG vaccines for percutaneous administration and 5 lots of BCG vaccines for intradermal administration were analyzed in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…However, this method is highly subjective. In 2017, Gweon et al demonstrated that the CV% between different laboratories can be as high as 95% (with an average of 49%) when using CFU assay for analysis 20 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, this method is highly subjective. In 2017, Gweon et al demonstrated that the CV% between different laboratories can be as high as 95% (with an average of 49%) when using CFU assay for analysis 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, flow cytometry assays were developed based on the use of highly sensitive laser-based flow cytometer technology for cell counting 14 , 20 . In this case, two strategies can be employed, known as dye-exclusion and dye-uptake 21 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations